Investigations of water droplet impact and freezing on a cold substrate with the Lattice Boltzmann method - Jesús García Pérez (Elsevier, 2021)
A multiphase Lattice Boltzmann model with phase change is presented for studying droplet impact and solidification on an airfoil. The proposed model combines a pseudo-potential multiphase model and a thermal single-component phase change model. These two models are verified separately. The pseudo-potential model with the Peng–Robinson equation of state is used to simulate large density ratios of multiphase flows. The thermal model is based on the total enthalpy and allows the phase change without using an iterative methodology. The coupling is made through the immersed moving boundary method that handles the solid–liquid interface. The generalization for curved surfaces is introduced through to a novel extrapolation method at boundaries. The effects of surface wettability, static contact angle and initial velocity of the droplet on the evolution of solid fraction and total freezing time are discussed and compared to other simulation and experimental works.